2021
DOI: 10.2147/clep.s304332
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Cancers After Gastric Cancer, and Gastric Cancer as Second Primary Cancer

Abstract: Background Second primary cancers (SPCs) are increasing, which may negatively influence patient survival. Gastric cancer (GC) has poor survival and when it is diagnosed as SPC it is often the cause of death. We wanted to analyze the risk of SPCs after GC and the risk of GC as SPC after any cancer. Such bidirectional analysis is important in relation to fatal cancers because SPCs may be under-reported in the short-term survival period. Methods Cancers were obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…These findings suggest that proper screening for other cancers after a diagnosis of GC may be crucial for these patients. A previous study from the Swedish Cancer Registry, conducted from 1990 to 2015, also revealed that patients with GC have a significantly increased risk of developing secondary primary cancers, such as small intestinal, esophageal, and kidney cancers [ 36 ]. Thus, it is important for patients with GC to be aware of their increased risk for other cancers and to undergo appropriate follow-up and screenings.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that proper screening for other cancers after a diagnosis of GC may be crucial for these patients. A previous study from the Swedish Cancer Registry, conducted from 1990 to 2015, also revealed that patients with GC have a significantly increased risk of developing secondary primary cancers, such as small intestinal, esophageal, and kidney cancers [ 36 ]. Thus, it is important for patients with GC to be aware of their increased risk for other cancers and to undergo appropriate follow-up and screenings.…”
Section: Discussionmentioning
confidence: 99%
“…With technological advances in the diagnosis and treatment of GC, the number of survivors with new primary malignant tumors has been increasing each year ( Sung et al, 2021 ). According to the latest cancer report, the incidence of GC together with MPMNs ranges from 3.4% to 7.3% ( Zheng et al, 2021 ), and the 10-year cumulative mortality due to GC with MPMNs is 1.5–2 times higher than that due to single GC ( Morais et al, 2020a ). However, because of the sporadic clinical onset of GC with MPMNs and the lack of international standardized treatment guidelines, clinicians have a poor understanding of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide population-based studies in Japan, Taiwan, United States of America, Portugal, and Sweden are available and listed in Table 2 [ 20 , 21 , 22 , 23 , 24 ]. The incidence of SPCs in patients with gastric cancer ranges from 4.4% to 5.5%.…”
Section: Epidemiology Of Spcsmentioning
confidence: 99%